2000
DOI: 10.1021/es990827x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Subsurface Catabolic Gene Frequencies during Natural Attenuation of Petroleum Hydrocarbons

Abstract: Public reporting burden for this collection of information Is estimated to average 1 hour per response. Including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. AUTHOR(S)Stapleton, Raymond D.; Sayler, Gary S.; Boggs, Mark; Libelo, Laurence; Stauffer, Thomas; Macintyre, William G. FUNDING NUMBERSC -F08637-94-C-6037 PE -62202F JON -1900C301 PERFORMING ORGANIZATION NAME(S) AND ADDRESS(ES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…This may to some extent explain the higher biodegradation of ethylbenzene compared to benzene in our study. Adaptation of indigenous microorganisms to exposure of BTEX hydrocarbons has been demonstrated by others [10,11] and in this study. To simulate the reaction of the soil microorganisms after an oil spill, we renounced on soil ageing and started measurements immediately after contaminating the soil.…”
Section: Discussionsupporting
confidence: 80%
“…This may to some extent explain the higher biodegradation of ethylbenzene compared to benzene in our study. Adaptation of indigenous microorganisms to exposure of BTEX hydrocarbons has been demonstrated by others [10,11] and in this study. To simulate the reaction of the soil microorganisms after an oil spill, we renounced on soil ageing and started measurements immediately after contaminating the soil.…”
Section: Discussionsupporting
confidence: 80%
“…While in some studies alkB homologs were detected in 10-40% of the bacterial population [97,101,102], other groups did not detect alkB homologs at all [99,100]. AlkB homologs that are closely related to the P. putida GPo1 enzyme appear to be common in gram-negative strains only (probably pseudomonads) [76].…”
Section: Environment/source Methods Conclusion For Alkb Homologs Refmentioning
confidence: 91%
“…Alaskan sediments Colony hybridization with alkB 39% of viable heterotrophs from uncontaminated soil contain alkB gene probe 67% of viable heterotrophs from contaminated soil contain alkB [97] Contaminated soil PCR followed by Southern blot Detection and quantification of alkB (and other genes) in soil: 1-10 with alkB gene probe gene copies per gram of soil can be detected [98 Variety of cold ecosystems PCR, and Southern blots None of the psychrophilic alkane degraders possess genes with alkB gene probe with high homology to P. putida alkB [99] Fuel oil-contaminated site Dot-blots DNA extracted from soil shows no significant hybridization with an alkB-gene probe [100] Shallow aquifer Southern blots 10-20% of the total bacterial community hybridizes with alkB gene probe with an alkB gene probe [101] Various sources PCR with highly degenerate Most alkane-degrading strains contain distantly related alkB homologs (54 bacterial strains) primers for alkB homologs (homology not sufficient for Southern or dot-blots) [50] Shallow aquifer Dot-blots with DNA extracted alkB genotypes start at 11% of total community, and peak at (natural attenuation site) from aquifer samples 52% after injection of synthetic jet fuel in the aquifer [102] Various sources Southern, colony and dot-blots, alkB genes (close homologs) are widespread only in short-chain n-alkane (54 bacterial strains) PCR followed by Southern degrading pseudomonads [76] Rhizosphere vs. bulk soil Multiplex PCR At a contaminated site alkB was 10 times more prevalent in the endophytic community compared to the bulk soil community [103] Propane and butaneDot-blots 8 of 15 strains (including pseudomonads and rhodococci) utilizing bacteria gave a strong signal, and 7 a weak signal with the IMT37 gene [37] Land treatment unit (LTU) PCR, terminal restriction alkB increased in abundance during the first 3 weeks of LTU operation, fragment length polymorphism and comprised > 80% of the total PCR products [104] Arctic and Antarctic soil PCR-hybridization Rhodococcal alkB genes occur in contaminated and pristine soils, and colony hybridization P. putida alkB occurs more frequently in contaminated soils [105] similar genes in other butane degraders (pseudomonads, rhodococci and unidentified bacteria). In a dot-blot experiment, 8 out of 15 propane or butane-degrading bacteria gave a strong signal with the gene-probe, while the remaining 7 gave a weak but detectable signal [37].…”
Section: Environment/source Methods Conclusion For Alkb Homologs Refmentioning
confidence: 99%
“…16S rRNA clone libraries). Studies involving isolations from contaminated sites have also typically reported microorganisms belonging to the phyla Proteobacteria and Actinobacteria (Cavalca et al 2004;Fahy et al 2008b;Hendrickx et al 2006;Stapleton et al 2000). For example, one study found that 86.9% of 300 gasoline-degrading isolates, were pseudomonads (Ridgway et al 1990).…”
Section: Introductionmentioning
confidence: 99%